2019
DOI: 10.2478/agri-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Choice of Suitable Conditions for Wheat Genetic Transformation

Abstract: Wheat is one of three most important cereals worldwide. Its production rises every year. There is a possibility to improve quantitative and qualitative parameters by biolistic method of transformation. The process of introduction of desired gene into the wheat genome and plant regeneration is affected by many factors. To identify the suitable conditions, selection system, the influence of donor, plant environment and the regeneration capacity of wheat genotypes were tested. The scutella of immature embryos ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The improvement of grain productivity and its components of winter wheat through exploiting of trivial or novel methods of plant transformation lead to creation of new varieties with improved traits. The use of new breeding methods has become an important technique to optimize plant structure for bioproductivity (Naveed et al, 2015;Klčová et al, 2019). One strategy to meet this challenge is to raise grain productivity by optimizing plant structure.…”
Section: Introductionmentioning
confidence: 99%
“…The improvement of grain productivity and its components of winter wheat through exploiting of trivial or novel methods of plant transformation lead to creation of new varieties with improved traits. The use of new breeding methods has become an important technique to optimize plant structure for bioproductivity (Naveed et al, 2015;Klčová et al, 2019). One strategy to meet this challenge is to raise grain productivity by optimizing plant structure.…”
Section: Introductionmentioning
confidence: 99%
“…Other lines turned to be far worse. Unlike previous studies (Nazarenko and Izhboldin, 2017;Nazarenko et al, 2019a), the significance of a beneficial mutation process for such traits as semi-dwarfism (for individual genotypes) and stunting (Nazarenko et al, 2019b) has been shown, that is, it has been proved that the mutation is a reliable and permanent source for the local genetic resources (Hongjie et al, 2019) related to such traits, and that obtaining high-intensity stunting strains with a long grained spike (Keser et al, 2022) of early ripeness (Klčová et al, 2019;Kirova et al, 2021) and intense wax accumulation (Cann et al, 2022) (to eliminate the negative effects of drought) based on local material is quite possible and regular (Kirova et al, 2021).…”
Section: Resultsmentioning
confidence: 85%